2011
DOI: 10.1038/aps.2010.200
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of glomerulosclerosis with all-trans retinoic acid is linked to decreased plasminogen activator inhibitor-1 and α-smooth muscle actin

Abstract: Aim: To examine the effects of all-trans retinoic acid (atRA) on renal morphology and function as well as on renal plasminogen activator inhibitor-1 (PAI-1) expression and plasmin activity in rats with 5/6 nephrectomy. Methods: Adult male Sprague Dawley rats were given 5/6 nephrectomy or sham operation. Renal function was measured 2 weeks later. The nephrectomized rats were assigned to groups matched for proteinuria and treated with vehicle or atRA (5 or 10 mg/kg by gastric gavage once daily) for the next 12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 54 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…Some investigations [1416] reported that ATRA could play a protective role in some renal diseases, but the detailed mechanism was not clear. Interestingly, ATRA treatment can suppress the generation of ROS [12], and have an anti-oxidative effect [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations [1416] reported that ATRA could play a protective role in some renal diseases, but the detailed mechanism was not clear. Interestingly, ATRA treatment can suppress the generation of ROS [12], and have an anti-oxidative effect [17].…”
Section: Introductionmentioning
confidence: 99%
“…The interstitial space is very sparse and not detectable, and the expression of a-SMA is exclusively confined in the intrarenal arteries in WKY groups. 27 It is possible that tubular epithelial cells, mesangial cells, and interstitial cells can transform into myofibroblasts, and these changes reflect dedifferentiation of renal tissue during the injury/repair process (hypertensive). The present results showing enhanced expression of CTGF, a-SMA, and collagen-III in the kidney with glomerular sclerosis and interstitial fibrosis, predicts a disrupted interaction between podocytes and CTGF.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those reported elsewhere. 15,16 Activation of the RAAS contributes to the pathogenesis and progression of renal diseases. ACE1, a key enzyme of the RAAS, can convert the inactive angiotensin I into the vasoactive and aldosterone-stimulating peptide angiotensin II.…”
Section: Discussionmentioning
confidence: 99%